2011
DOI: 10.1083/jcb.201009119
|View full text |Cite
|
Sign up to set email alerts
|

Actin polymerization driven by WASH causes V-ATPase retrieval and vesicle neutralization before exocytosis

Abstract: WASH coats mature lysosomes and is required for exocytosis of indigestible material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
188
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(197 citation statements)
references
References 37 publications
7
188
2
Order By: Relevance
“…1A and Movie S1). Consistent with previous observations of both Dictyostelium postlysosomes and mammalian endosomes (23,24,27), GFP-WASH was restricted to multiple discrete subdomains on the macropinosome surface. This observation indicates a previously unrecognized role for WASH in early macropinosome maturation.…”
Section: Wash Is Recruited To Early Macropinosomes and Phagosomessupporting
confidence: 78%
See 3 more Smart Citations
“…1A and Movie S1). Consistent with previous observations of both Dictyostelium postlysosomes and mammalian endosomes (23,24,27), GFP-WASH was restricted to multiple discrete subdomains on the macropinosome surface. This observation indicates a previously unrecognized role for WASH in early macropinosome maturation.…”
Section: Wash Is Recruited To Early Macropinosomes and Phagosomessupporting
confidence: 78%
“…Previously, we showed that a late phase of WASH activity drives the sorting and removal of the V-ATPase during Dictyostelium lysosome to postlysosome transition (27). This finding occurred via direct interaction between the V-ATPase and WASH-generated actin, and arrival of WASH coincides with V-ATPase removal.…”
Section: Wash Is Recruited To Early Macropinosomes and Phagosomesmentioning
confidence: 99%
See 2 more Smart Citations
“…A similar role for WASH in the recycling of integrins has been seen in mammalian cells . Moreover, WASH regulates the retrieval of the vacuolar (V)-ATPase from post-lysosomal compartments, and the recycling of plasma membrane components from early macropinosomes and phagosomes in Dictyostelium (Buckley et al, 2016;Carnell et al, 2011). Thus, the ability of WASH to regulate receptor recycling and lysosome neutralization has been highly conserved throughout evolution.…”
Section: Jmymentioning
confidence: 99%